The Winchester »Weather-Vane« Reconsidered - Kjølbye-Biddle, Birthe (Hikuin, 1984)
On 17 December 1910 The Hampshire Chronicle reported that during excavations at the cathedral, under the south transept, there was found some 17 feet deep and in the peat, a metal strip or band with a curious, indeed elegant, decoration made up of interlaced slightly-raised work, which resembled somewhat Celtic Style. Near it was found a massive ring. On the following 16 March R.A. Smith exhibited this bronze panel to The Society of Antiquaries, noting that it was found at the south-east angle of the south transept, near a bronze ring, 18 inches (0.46 m.) below the top of the peat, the peat being 10 to 12 feet (3.0 to 3.6 m.) from the surface.